Impaired Stabilisation of Orthostatic Cerebral Oxygenation is Associated with Slower Gait Speed: Evidence from The Irish Longitudinal Study on Ageing. - Knight, Silvin; Kenny, Rose (My University, 2021)
Background: Cerebral autoregulation (CAR) systems maintain blood flow to the brain across a wide range of blood pressures. Deficits in CAR have been linked to gait speed (GS) but previous studies had small sample sizes and used specialized equipment which impede clinical translation. The purpose of this work was to assess the association between GS and orthostatic cerebral oxygenation in a large, community- dwelling sample of older adults. Method: Data for this study came from the Irish Longitudinal Study on Ageing. A near-infrared spectroscopy (NIRS) device attached to the forehead of each participant (n = 2 708) was used to track tissue saturation index (TSI; the ratio of oxygenated to total hemoglobin) during standing. GS was assessed using a portable walkway. Results: Recovery was impaired in slower GS participants with a TSI value at 20 seconds (after standing) of −0.55% (95% CI: −0.67, −0.42) below baseline in the slowest GS quartile versus −0.14% (95% CI: −0.25, −0.04) in the fastest quartile. Slower GS predicted a lower TSI throughout the 3-minute monitoring period. Results were not substantially altered by adjusting for orthostatic hypotension. Adjustment for clinical and demographic covariates attenuated the association between but differences remained between GS quartiles from 20 seconds to 3 minutes after standing. Conclusion: This study reported evidence for impaired recovery of orthostatic cerebral oxygenation depending on GS in community-dwelling older adults. Future work assessing NIRS as a clinical tool for monitoring the relationship between GS and cerebral regulation is warranted.
PUBLISHED
Keywords: Cardiovascular, Gait, Neuroimaging; Ageing